Memoria, fantasia e creazione artistica in Diderot - Pistolesi, Clara (Il sogno della farfalla, 2014)
The article offers an outline of an original research into the deeper dimension of the human mind in Denis Diderot’s works. The research starts by analyzing some pages from Lettre sur les sourds et muets (1751), Salon de 1767, Rêve de d’Alembert (1769) and the incomplete Éléments de physiologie (1765-1784), as well as from some letters addressed to Sophie Volland, in which we witness the connection between the theme of identity-memory, and the ideal model and artistic creativity. The intuition of a specific function of the intellect, i.e. the memory of facts and things experienced of which a man loses awareness, but which constitute his story and identity, allowed Diderot to perceive in a materialistic sense a reality which had previously been considered of a spiritual nature, thus pertaining to a religious sphere, or had been totally ignored. His research allows us to see a considerable difference with the philosophers which were his contemporaries, in that he speaks about an interior image which comes into being, unwittingly, and constitutes the grounds of thought and artistic creativity, of aesthetic and moral judgement.